Clinical Characteristics of Coronavirus Disease 2019 in Dr. Agoesdjam Regional Public Hospital, Ketapang, West Kalimantan, Indonesia - Herick Alvenus Willim; Cristianto Cristianto; Yohana Roy Ito Br Sihombing; Eva Lydia Munthe; Widi Mujono; Enny Enny (Masters Program in Public Health, 2020)
Background: Coronavirus disease 2019 (COVID-19) is a new pandemic caused by SARS-CoV-2 infection. COVID-19 has spread to almost all countries with increasing cases, including Indonesia. Data on the clinical characteristics of COVID-19 in Indonesia is still limited. This study aimed to determine the clinical characteristics of COVID-19.Subjects and Method: This study was a descriptive study with a retrospective design conducted in Dr. Agoesdjam Regional Public Hospital. The data were obtained from the medical records of all patients with confirmed COVID-19 from April 1 to July 31, 2020. There were 50 patients as the sample of the study. The data collected were demographics, expo